Morphological characteristics of neuromuscular junctions of the opossum (Didelphis albiventris) extraocular muscles: a scanning-electron-microscopic study - Matheus, Selma Maria Michelin [UNESP]; Soares, J. C. [UNESP] (S. Karger AG, Basel, 2000)
Three types of neuromuscular junctions were described in the extraocular muscles of the opossum. The present study demonstrates the three-dimensional characteristics of these neuromuscular junctions after HCl connective tissue digestion. Adult opossum of both sexes were used and the neuromuscular junctions of the extraocular muscles were examined after removal of the intramuscular connective tissue and basal layer. This material was examined with a scanning electron microscope. Two types of 'en plaque' neuromuscular junction were described: the continuous type revealed elongated and branched primary synaptic grooves separated from each other by sarcolemma protuberances with different sizes, and the discontinuous or punctiform type which presents very shallow and discontinuous grooves when compared with the former. The multiple neuromuscular junctions were observed as two or three junctions associated with the same muscular fiber. The multiple junctions were present in thin fibers (around 11 microm caliber); the en plaque junctions were associated with large diameter fibers (around 21 microm). This study confirms and reveals the detailed morphological characteristics of the three neuromuscular junction types previously described by transmission electron microscope in the extraocular muscles of opossum.
Keywords: Extraocular muscles; Neuromuscular junction; Scanning electron microscope; Opossum